Prediksi Jumlah Siswa Baru Menggunakan Single Exponential Smooth (Studi Kasus : SMA Dharmawangsa) - Bunaya Arthavia Sitorus; Rizki Muliono (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2023)
Prediction is the process of systematically estimating the most likely event to occur in the future based on past and current information, so that errors (the difference between what happened and what is expected) are minimized. Dharmawangsa High School has the goal of adding/improving school facilities and infrastructure. Therefore, a solution must be found to overcome this problem, one of which is predicting the number of new Dharmawangsa High School students so that the Dharmawangsa High School can predict the addition and reduction of school facilities and infrastructure. Because of this, researchers approached the solution by implementing the Single Exponential Smooth method and designing a system that is useful for predicting the number of new students at Dharmawangsa High School. From the research results, the number of new students in 2024 will be 299 science students and 101 social studies students. The smallest mean squared error (MSE) for the number of new science students was obtained with α=0.3, namely 1723,673 and the smallest MSE for the number of new social studies students with α=0.9, namely 1293,873. The smallest Mean Absolute Percentage Error (MAPE) for the number of new science students was obtained with α=0.6, namely 10.29% with a good description of the method used. Meanwhile, the smallest MAPE on the number of new IPS students was obtained with α=0.8, namely 26.64% with a description of the method used was bad. This study concludes that the Single Exponential Smooth Method can be used to predict the number of new students at Dharmawangsa High School so that the predicted value can be known in the following year. As well as researchers managed to build and design a system to predict the number of new students at Dharmawangsa High School.